Nctet-2k17 2017
DOI: 10.22161/ijaers/nctet.2017.eee.18
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Implementation for efficient PLC based low-power photovoltaic generation plants

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…Jerusalem, concluded that the mean C-reactive protein in Cerebrospinal fluid was 143 +/-2.1 mg/L in gram negative bacterial meningitis as compared to a value of 4 +/-0.9 mg/L in gram positive bacterial meningitis. 8 Similarly, in this study also among PM, CSF-CRP level was higher in those caused by Gram negative organisms as compared to Gram positive organisms.  A study conducted at JLN, Ajmer, Rajasthan, concluded that Cerebrospinal fluid-C-reactive protein levels in pyogenic meningitis were very high (104 +/-90.21 mg/L), but within normal range in TBM, viral meningitis and controls (< 6mg/L).…”
Section: Observation and Discussionsupporting
confidence: 71%
“…Jerusalem, concluded that the mean C-reactive protein in Cerebrospinal fluid was 143 +/-2.1 mg/L in gram negative bacterial meningitis as compared to a value of 4 +/-0.9 mg/L in gram positive bacterial meningitis. 8 Similarly, in this study also among PM, CSF-CRP level was higher in those caused by Gram negative organisms as compared to Gram positive organisms.  A study conducted at JLN, Ajmer, Rajasthan, concluded that Cerebrospinal fluid-C-reactive protein levels in pyogenic meningitis were very high (104 +/-90.21 mg/L), but within normal range in TBM, viral meningitis and controls (< 6mg/L).…”
Section: Observation and Discussionsupporting
confidence: 71%